TINGKAT AKSEPTABILITAS DIGITAL APLIKASI JAKARTA KINI (JAKI) BAGI PENYANDANG DISABILITAS - Mutiara Tri Apriyani Cahyadi; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
The digital transformation of Jakarta Smart City (JSC) aims to improve government transparency and access to public information for all Jakarta residents, including people with disabilities. However, limited inclusive features still affect service acceptability. This study measures the digital acceptability of the Jakarta Kini (JAKI) application for people with disabilities and identifies factors that hinder access. A mixed methods approach was used using a Likert-scale questionnaire to 100 respondents with disabilities in DKI Jakarta and observations of application usage. Data were analyzed descriptively, quantitatively and qualitatively. The results show that JAKI's digital acceptability is in the moderately accessible category, but there are still obstacles in the Perceivable and Operable dimensions, particularly in alternative text, visual contrast, and screen reader navigation. Factors influencing acceptability include technological accessibility, information openness, and inclusive facilities. This study emphasizes the importance of improving JAKI's digital accessibility to support transparent and inclusive governance in accordance with Law No. 14 of 2008.